INFLUENCE OF PEA SOWING RATES ON STRUCTURAL ELEMENTS AND GRAIN YIELDS - Lykhochvor, V.V.; Andrushko, M.O. (Scientific Progress & Innovations, 2019)
High yields of pea grain can be obtained by growing it using intensive technology with applying calculat-ed rates of mineral fertilizers and integral application of plant protection means. It is also important to op-timize the sowing rates of pea seeds in certain soil-climatic conditions. The aim of the study was to determine the effect of six sowing rates (0.9; 1.0; 1.1; 1.2; 1.3; 1.4 million/ha) on the indices of yield structure and grain productivity of Madonna pea variety. During the research the following methods were used: field, quantitative, method of test sheaf, weight, statistical. The results of the conducted studies have shown that changing the density of agro-phytocenosis affects the pea yield, which is explained by the formation of dif-ferent indicators of the crop structure. It was found that increasing the sowing rate from 0.9 million/ha to 1.4 million/ha led to the increase of plant density before harvesting from 70 pcs/m2 to 90 pcs/m2, or by 20 pcs/m2. However, this did not ensure the expected yield increase, since the individual productivity of the pea plants decreased in the densely sown areas. It was revealed that sowing rates significantly affected the structure of pea yield. As the seed sowing rate increased from 0.9 million/ha to 1.4 million/ha, the number of pods per plant decreased from 4.8 to 4.5 pcs, the number of grains in a pod – from 6.9 to 6.1 pcs, and the number of grains per plant – from 33 to 27.6 pcs. The main element of productivity, grain weight per plant decreased in densely sown areas from 9.60 g in the variant with the sowing rate of 0.9 million/ha to 7.05 g at sowing rate of 1.4 million/ha, i.e. by 2.55 g. Increasing the sowing rate was also accompanied by decreasing the weight of 1000 grains, from 291.0 g to 255.8 g, respectively. The optimal sowing rate of Madonna pea variety under sufficient and excessive moistening (in 2017 the rainfall was 761 mm, in 2018 − 818 mm, and in 2019 − 803 mm) of the Western Forest-Steppe of Ukraine is 1.0 and 1.1 million/ha., The grain yield in these variants was the highest, amounting to 6.52 t/ha and 6.55 t/ha. Such level of yield was obtained as a result of the rational combination of plant density before harvesting (77 and 82 pcs/m2) and the increase of grain weight per plant to 8.96 g and 8.51 g. The increase and decrease of sowing rate over 1.0 and 1.1 mil-lion / ha causes yield decreasing.